(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Hyperlipidemia or hyperlipoproteinemia involves abnormally elevated levels of any or all lipids and/or lipoproteins in the blood. It has been proved beyond doubt that hyperlipidemia is one of the major modifiable risk factors for cardiovascular diseases. Statins are mostly preferred in the clinical management of hyperlipidemia. But in situations where the desired results are not achieved in spite of adequate statin therapy or statins are contraindicated or not tolerated, the physicians seek for a safer and effective alternative. Many herbal products have been studied extensively for their anti-hyperlipidaemic properties. Guggulu (Commiphora mukul), Rasona (Allium sativum) etc are few examples out of them. In this comparative clinical study a poly herbal formulation (Cholest Guard) was clinically evaluated in 27 patients with hyperlipidemia. 25 patients in the control group were treated with Atorvastatin. Both Cholest Guard and Atorvastatin significantly reduced total cholesterol, LDL, VLDL and triglyceride levels and increased HDL level. The results were comparable. Cholest Guard was safe and devoid of any adverse effects. However Atorvastatin produced undue side effects like muscle pain, headache, nausea, sleep disturbance& Gastric upset. The LFT profile was also altered in some cases showing that Atorvastatin has deleterious effect on the liver.